Activities Written by Prospective Primary Teachers on Realistic Mathematics Education - Hatice Kübra Güler (International Journal of Evaluation and Research in Education (IJERE), 2018)
It is important for students to connect with real life in mathematics courses. The aim of this study is to investigate the activities which are written by prospective primary school teachers in the context of Realistic Mathematics Education. This research is a case study of which data were collected by qualitative methods. The participants of the research included 81 prospective primary teachers who are junior students attended primary teacher department. It was asked them to write an activity suitable for primary mathematics curriculum by considering Realistic Mathematics Education principles. They were given one month to write the activities. The activities written by prospective teachers analyzed by descriptive methods in terms of learning domains, types of context and principles of Realistic Mathematics Education. Totally 36 activities were written by prospective teachers. Based on the analysis, it was observed that not all the contexts were exactly real life contexts. It was determined that prospective teacher could not distinguish routine word problems from real life problems. It can be said that theoretical knowledge of Realistic Mathematics Education is inadequate for writing activities and prospective primary teachers need to practice on writing activities regarding the mentioned theory.